Pedagogical Reflection to Improve Professionalism of Islamic Education Teacher (GPAI) at Junior High School (SMP) Level through Applicable Design of Educational Curriculum and Professional Teacher Training (PLPG) in 2013 - Amiruddin Siahaan; Taufiqurrahman Taufiqurrahman; Nurhidayah Nurhidayah (Institut Agama Islam Negeri Imam Bonjol Padang, 2015)
Educational curriculum and teacher certification training (PLPG) is structured to ensure that participants are able to absorb learning materials and carry out its function as educators, teachers, counselors, and coaches. PLPG is a tool that allows teachers to carry out its functions effectively so that the wider implications for the learning process. Through the curriculum of teacher professionalism is pursued inherent in life and the life of the teacher. Professionalism attached to it can be seen from the reflection that they appear in everyday life in a pedagogical context, personality, professional, and social.Â Copyright Â© 2015 by Al-Ta'lim All right reserved